RPA prevents G‐rich structure formation at lagging‐strand telomeres to allow maintenance of chromosome ends. (3rd June 2015) - Audry, Julien; Maestroni, Laetitia; Delagoutte, Emmanuelle; Gauthier, Tiphaine; Nakamura, Toru M; Gachet, Yannick; Saintomé, Carole; Géli, Vincent; Coulon, Stéphane
Abstract Replication protein A (RPA) is a highly conserved heterotrimeric single‐stranded DNA‐binding protein involved in DNA replication, recombination, and repair. In fission yeast, the Rpa1‐D223Y mutation provokes telomere shortening. Here, we show that this mutation impairs lagging‐strand telomere replication and leads to the accumulation of secondary structures and recruitment of the homologous recombination factor Rad52. The presence of these secondary DNA structures correlates with reduced association of shelterin subunits Pot1 and Ccq1 at telomeres. Strikingly, heterologous expression of the budding yeast Pif1 known to efficiently unwind G‐quadruplex rescues all the telomeric defects of the D223Y cells. Furthermore, in vitro data show that the identical D to Y mutation in human RPA specifically affects its ability to bind G‐quadruplex. We propose that RPA prevents the formation of G‐quadruplex structures at lagging‐strand telomeres to promote shelterin association and facilitate telomerase action at telomeres.